Authenticating Oral and Memory Variants in Ancient Hebrew Literature - Tooman, William A. (Journal of Semitic studies, 2019)
The purpose of this essay is to consider the authentication of oral and memory variants in ancient Hebrew literature. I compare types of textual dissimilarity that are associated with scribal errors of hearing or memory with types of dissimilarity that occur regularly in two other types of textual reproduction - quotations and inner-biblical citations. Dissimilarity is the norm with quotations and citations, and the types of dissimilarity generated by quotations and citations are identical to types of dissimilarity that are commonly identified as aural or memory-variants. An author, placing the same utterance in the mouths of two characters (or twice in the mouth of single character) will typically render that utterance with difference. Difference is, if anything, even more characteristic of inner-biblical citations. This serves as a note of caution about too readily drawing conclusions regarding the causes of dissimilarity or the process of recall implied by them and cautions against overestimating the presence and significance of oral and mental features in biblical and Second Temple literature.